Psychological Detachment as a Mediator Between Successive Days' Job Stress and Negative Affect of Teachers - Aulén, Anna-Mari; Pakarinen, Eija; Feldt, Taru; Tolvanen, Asko; Lerkkanen, Marja-Kristiina (Frontiers in Education, 2022)
The study investigated the mediating role of teachers’ psychological detachment between subsequent days’ job stress and negative affect. Fifty-seven Finnish teachers answered to a mobile diary four times a day on two successive workdays assessing their negative affect, three times a day assessing their job stress and once a day after work assessing their psychological detachment from work. Two-level modelling on both the between individual level and within day level was used to test the mediational model. The data supported the mediational model where teachers’ job stress hinders their psychological detachment, which again increases their negative affect and job stress on the subsequent day. On the basis of our results teachers’ occupational health interventions intended to reduce their job stress and support their psychological detachment from work are desirable. In addition, robust work-home segmentation norms within schools are suggested to support teachers’ psychological detachment from work.